71.0k views
3 votes
How do you do this and what is the answer?

How do you do this and what is the answer?-example-1
User Kedar
by
5.8k points

2 Answers

5 votes

Answer:

a)
f(-4) = 19

b)
f(0) = 3

Explanation:

When working with these type of problems, they give you a function, which in this case is
f(x), and they give you what that function is equal to, it's value, which in this case is
x^(2) + 3.

  • When working with letter a), the function is
    f(-4), meaning all the variables in the expression will be -4.
  • When working with letter b), the function is
    f(0), meaning all the variables in the expression will be 0.

First let's work with letter a), (-4).


f(x) = x^(2) + 3


f(-4) = -4^(2) + 3


f(-4) = 16 + 3


f(-4) = 19

Let's now work with letter b), (0).


f(x) = x^(2) + 3


f(0) = 0^(2) + 3


f(0) = 0 + 3


f(0) = 3

Hope it helped,

BiologiaMagister

User Tchevrier
by
5.6k points
4 votes

Answer:

a.) 19

b.) 3

Explanation:

a.)

f(x) = x² + 3, f(-4)

f(-4) = (-4)² + 3

f(-4) = 16 + 3

f(-4) = 19

b.)

f(x) = x² + 3, f(0)

f(0) = (0)² + 3

f(0) = 0 + 3

f(0) = 3

Thus, f(-4) = 19 and f(0) = 3

-TheUnknownScientist

User Michael Liao
by
5.8k points